Modernizing public health communication competencies in Canada: A survey of the Canadian public health workforce - McAlpine, Devon; MacKay, Melissa; Grant, Lauren E.; Papadopoulos, Andrew; McWhirter, Jennifer E. (Canadian journal of public health, 2024)
Objectives Since the publication of the Core Competencies for Public Health in Canada in 2008, the public health and communication landscape has changed dramatically. Digital media and infodemics have shifted how practitioners must communicate and respond to health information. The age of the current competency framework, which is relied on for workforce development, alongside emerging public health challenges, have prompted calls for modernized competency statements. This study aims to (i) measure self-reported communication competence in the public health workforce, (ii) measure agreement with new communication competency statements, (iii) identify variation in agreement between sub-groups of professionals, and (iv) explore current and needed communication training. Methods Using a mixed-methods online survey, a sample of 378 participants in various Canadian public health roles and regions were asked to rate their current communication competence and agreement with a modernized, evidence-based draft communication competency framework. The survey was distributed in both official languages through partner organizations and social media. Descriptive statistics were performed to assess agreement and variation was analyzed in relation to public health roles and experience. Results While most participants self-reported communication competence, specific areas were rated lower. All 21 proposed competency statements received high agreement with some variation observed between expertise and experience levels. Demand for communication training is high. Conclusion Strong agreement with statements indicates support for a modernized communication competency framework among sampled professionals. Research to gather more evidence surrounding the communication demands of the public health workforce and observed variation in strong agreement for the proposed statements is underway.